Il teatro della traduzione: una performance estetica? - Nardelli, Elena (Aesthetica Preprint, 2025)
This work aims to exploit the conceptual resources developed by aesthetic theories of the performative for a better understanding of the practice of translation. The argument is threefold. First, it argues that the aesthetics of performance can prompt translation to question the pivotal elements of its own conceptual framework, first and foremost the centrality of the original text, understood as an autonomous work of art in its own right from which a potentially infinite number of translations may emerge (like effects from a cause). Second, performance can illuminate translation’s status as an embodied and situated activity carried out by a flesh-and-blood human being who is constantly confronted with the materiality of word and language and with her own particular experience. Third, the aesthetics of performance can lead translation theory to urgently rethink the notion of meaning, conceived no longer as a pre-constituted element that precedes translation but as an element that is regenerated in the crisis of translation.